2010
DOI: 10.1136/hrt.2009.188391
|View full text |Cite
|
Sign up to set email alerts
|

Acute coronary occlusion in non-ST-elevation acute coronary syndrome: outcome and early identification by strain echocardiography

Abstract: Patients with NSTEMI due to acute coronary occlusions develop larger infarcts and more impaired left ventricular function than patients with NSTEMI without occlusions, regardless of infarct-related territory. Territorial circumferential strain by echocardiography enables very early identification of acute coronary occlusions in patients with NSTE-ACS and may be used for detection of patients requiring urgent revascularisation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
88
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(98 citation statements)
references
References 32 publications
5
88
0
5
Order By: Relevance
“…Also, a significant difference was found between the two groups concerning the segmental strains (P < 0.05), except for the posterior segment (P > 0.05). This was consistent with the results of the previous studies, demonstrating the capability of STE to detect ischemic changes (11,15,16).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Also, a significant difference was found between the two groups concerning the segmental strains (P < 0.05), except for the posterior segment (P > 0.05). This was consistent with the results of the previous studies, demonstrating the capability of STE to detect ischemic changes (11,15,16).…”
Section: Discussionsupporting
confidence: 82%
“…Electrocardiography (ECG) or cardiac biomarkers cannot exactly distinguish acute occlusion. Therefore, finding available, simple, fast methods seems to be necessary (15). In the current management, echocardiography along with cardiac perfusion scan and Exercise Tolerance Test (ETT) are used as pre-angiographic modalities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ponadto można uwidocznić upośle-dzoną funkcję odcinkową za pomocą analizy odkształcenia (strain) i tempa odkształcenia (strain rate). Obie te techniki mogą poprawiać diagnostyczną i prognostyczną wartość konwencjonalnej echokardiografii [60,61]. Dodatkowo echokardiografia może być przydatna w wykrywaniu innych stanów przebiegających z bólem w klatce piersiowej, takich jak ostre rozwarstwienie aorty, płyn w osierdziu, zwężenie zastawki aortalnej, kardiomiopatia przerostowa lub poszerzenie prawej Rycina 3.…”
Section: Ocena Czynnościowaunclassified
“…The benefit of early revascularisation by means of percutaneous coronary intervention (PCI) or thrombolysis is well documented for cases of myocardial infarction with ST segment elevation on the ECG (STEMI), where most of the patients have acute coronary occlusion (2,3). In recent years it has been demonstrated that an ECG alone does not identify acute coronary occlusion in all patients (4,5). Coronary angiography also reveals coronary occlusion in many myocardial infarctions without ST elevation in the ECG (NSTEMI) (6,7).…”
Section: Resultsmentioning
confidence: 99%